Досліждення поведінки пружної коливальної системи з нелінійним віброгасником в околі резонансу - Плаксій, Катерина Юріївна; Міхлін, Юрій Володимирович (Запорізький національний університет, 2014)
Розглядається задача дослідження резонансної поведінки пружної коливальної системи з нелінійним віброгасником під впливом зовнішнього гармонічного збурення. Застосована методика зведення до редукованої системи відносно змінних енергії, арктангенса відношення амплітуд та різниці фаз розв’язків. Аналіз рівнянь редукованої системи дозволяє оцінити стійкість форм коливань, виявити локалізацію енергії на координатах і появу біфуркацій в околі резонансів. Зокрема, для розглянутої коливальної системи методика дозволяє виявити так звані перехідні форми коливань. Результати чисельних експериментів підтверджують успішність запропонованої методики.

Рассматривается задача исследования резонансного поведения упругой колебательной системы с нелинейным виброгасителем под воздействием внешнего гармонического возмущения. Применена методика сведения к редуцированной системе относительно переменных энергии, арктангенса отношения амплитуд и разности фаз решений. Анализ уравнений редуцированной системы позволяет оценить устойчивость форм колебаний, выявить локализацию энергии на координатах и появление бифуркаций в окрестности резонансов. В частности, для рассмотренной колебательной системы методика позволяет выявить так называемые переходные формы колебаний. Результаты численных экспериментов подтверждают успешность предложенной методики.

Dynamics of dissipative elastic system with a nonlinear vibration absorber under external harmonic excitation is considered in the vicinity of external resonance on some fundamental frequency. The Kauderer-Rosenberg concept of the nonlinear normal modes, which is based on determination of trajectories in the system configuration space, is used. Vibration modes in dissipative systems are not the classical Kauderer-Rosenberg vibration modes, and such regimes contain an exponential decrease of vibration amplitudes. Besides, so-called transient nonlinear normal modes, which exist only for some value of the system energy, that is, for some instant of time, can be observed in resonance vicinity for systems under external excitation. Other motions of the dissipative system can approach to these modes when the system energy is close to some specific energy value. Transformation to the reduced system which is stated with respect to the system energy, an arctangent of the amplitudes ratio and a difference of phases of solutions is applied. An analysis of the reduced system’s equations allows to estimate the vibration mode stability, to reveal the energy localization on coordinates and the appearance of new motions in resonance regime. In particular, for the considered system the technique allows to estimate bifurcation conditions in vicinities of resonances and to reveal the transient vibration modes. For a case of resonance on the first fundamental frequency it was obtained that the mode of energy localization on the first main coordinate is steady and we can see a transfer of other motions to this vibration mode. Respectively for a resonance case on the second fundamental frequency the mode of energy localization on the second main coordinate is steady and attracting. In both cases an appearance of the transient nonlinear normal modes of coupled vibrations is observed. Simultaneously an investigation of stability and bifurcation of vibration modes, their interaction and the energy transfer from one mode to another one are considered. Conditions of energy localization on a vibration absorber are received. Results of numerical simulation confirm an accuracy of the proposed analytical approach.
Исследование поведения упругой колебательной системы с нелинейным виброгасителем в окрестности резонанса
Research of Behavior of Elastic Oscillatory System with f Nonlinear Vibration Absorber in Resonance Vicinity
Keywords: стійкість; локалізація; редукована система; перехідна нелінійна нормальна форма; устойчивость; локализация; редуцированная система; переходная нелинейная нормальная форма; stability; localization; reduced system; transient nonlinear normal mode